1997
DOI: 10.1002/(sici)1097-4644(19971101)67:2<275::aid-jcb13>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel nuclear matrix protein HET binds to and influences activity of the HSP27 promoter in human breast cancer cells

Abstract: Since the small heat shock protein hsp27 enhances both growth and drug resistance in breast cancer cells, and is a bad prognostic factor in certain subsets of breast cancer patients, we have characterized the transcriptional regulation of hsp27, with the long-term goal of targeting its expression clinically. The majority of the promoter activity resides in the most proximal 200 bp. This region contains an imperfect estrogen response element (ERE) that is separated by a 13-bp spacer that contains a TATA box. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 0 publications
0
38
0
2
Order By: Relevance
“…Furthermore, in addition to the findings of our group, the specific VDRE and ERE regulatory control by ‘non-receptor’ response element binding proteins has been endorsed by the involvement of other non-related components such as the ubiquitous transcription regulator YY1 (i.e. Ying Yang 1, a GLI-Kruppel class of zinc finger protein) (29) and the scaffold attachment factor B (30), respectively. These findings provide additional evidence for the complex regulation of steroid hormones and their receptors targeting VDREs and EREs in different cellular systems.…”
Section: Hormone Response Element (Hre) Interactorsmentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, in addition to the findings of our group, the specific VDRE and ERE regulatory control by ‘non-receptor’ response element binding proteins has been endorsed by the involvement of other non-related components such as the ubiquitous transcription regulator YY1 (i.e. Ying Yang 1, a GLI-Kruppel class of zinc finger protein) (29) and the scaffold attachment factor B (30), respectively. These findings provide additional evidence for the complex regulation of steroid hormones and their receptors targeting VDREs and EREs in different cellular systems.…”
Section: Hormone Response Element (Hre) Interactorsmentioning
confidence: 65%
“…Also, G-protein mutations (e.g. GNAS1) cause Albright's hereditary osteodystrophy (30), which leads to intramembranous ossifications progressively developed from the dermis.…”
Section: Hormone Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…SAF-B is a nuclear matrix-associated factor inactivated by active caspase-3 and involved in the regulation of HSP27. 19,20 Decreased level of HSP27 was observed in cotreated MA-11 cells (Fig. 3B, left panel).…”
Section: Its In Combination With Tpmp-i-2 Results In Inactivation Of Parpmentioning
confidence: 87%
“…The locus control regions bind to multiple transcription factors that cooperate synergistically to activate gene transcription. On the other hand, the MARs may act as specific landmarks that anchor DNA to the nuclear scaffold (28). It has been shown that a MAR, present on the ovine ␤-lactoglobulin gene, modulates basal transgene expression in transgenic mice (29).…”
Section: Tissue- Region- and Cell-specific Expression Of The 53mepmentioning
confidence: 99%